Analisis Kemampuan Pemecahan Masalah Matematika ditinjau dari Kepercayaan Diri Siswa pada Materi Himpunan di Kelas VIII SMP Torsina II Singkawang - Yosia Lapuni Ruka; Nurhayati Nurhayati; Buyung Buyung (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This study aims to describe the ability to solve mathematical problems from the perspective of students' confidence in the set material in grade VIII of SMP Torsina II Singkawang. This research method is a descriptive method with a qualitative research type. The subjects in this study are 32 grade VIII students. The object of this study is the ability to solve mathematical problems and students' confidence in the set material. The data collection instrument is in the form of a written test in the form of a description in accordance with indicators of mathematical problem-solving ability, confidence questionnaires and interviews that have been tested with the validity of the content, validity of the construct, reliability, level of difficulty and discriminating power. The overall results of the study showed that the level of confidence and mathematical problem-solving ability of grade VIII students at SMP Torsina II Singkawang in the set material had a medium category. While specifically showing that: 1) there is a significant relationship between confidence and mathematical problem-solving ability, which means that if confidence increases, students' mathematical problem-solving ability also increases and vice versa; 2) the form of mistakes made by students in solving problems with mathematical problem-solving skills in the set material in the form of errors in understanding problems, errors in using formulas or principles, errors in process or operation skills, and errors in drawing conclusions or checking the correctness of the results obtained.